2021
DOI: 10.1101/2021.01.05.424557
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Allosteric modulators enhance agonist efficacy by increasing the residence time of a GPCR in the active state

Abstract: Metabotropic glutamate receptors (mGlu) are G protein-coupled receptors that represent promising targets for brain diseases. Much hope in drug development come from the discovery of positive allosteric modulators that display subtype selectivity, and act by increasing agonist potency, as well as efficacy in most cases. How such compounds can influence agonist efficacy remains unclear. Here, we explore the structural dynamics of the full-length mGlu2 dimers at submillisecond timescales using single molecule FRE… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 73 publications
2
14
0
Order By: Relevance
“…In contrast, the PAM that binds in the 7TM domain is strictly required to stabilize the fully reoriented VFTs in the active state, even though this effect to increase efficacy remains dependent of the orthosteric agonist. We note that these observations are perfectly consistent with those we previously obtained using SNAP-tagged receptors, labeled at the level of the upper lobes as well 17 .…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…In contrast, the PAM that binds in the 7TM domain is strictly required to stabilize the fully reoriented VFTs in the active state, even though this effect to increase efficacy remains dependent of the orthosteric agonist. We note that these observations are perfectly consistent with those we previously obtained using SNAP-tagged receptors, labeled at the level of the upper lobes as well 17 .…”
Section: Resultssupporting
confidence: 92%
“…Control LRET titration experiments on SNAP-tag labeled receptors confirmed unimpaired functional integrity over time at room temperature and demonstrated that the C-terminal modifications do not impair receptor stimulation by Glu and allosteric modulation by BINA ( Figure S6a-d ). In addition, the same constructs were analyzed by smFRET, which confirmed that intersubunit VFT reorientation occurs in an identical manner on these C-terminally modified constructs as on wildtype receptors (as in 17 ) in the absence of ligands or when saturated with LY341495, Glu, Glu + Gi and Glu + BINA ( Figure S7a-e ).…”
Section: Resultssupporting
confidence: 54%
See 3 more Smart Citations